Comparative Perspectives: Federal and International Models as an Inspiration for EU Member State Equality - Flander, Benjamin (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
This chapter explores how selected federal states, confederations, and international organisations with supranational elements compare to the EU in terms of structure and functioning and whether they can serve as models for strengthening equality amongst EU Member States. The author examines (con)federalism and supranationalism as concepts of governance and provides an analysis of the structural and functional characteristics of selected (con)federal systems and international organisations with supranational elements, focusing specifically on the implementation of the principle of equality amongst their constituent parts. In doing so, the goal is to determine whether federal, confederal, and supranational governance arrangements can offer valuable insights and inspiration for the EU. The definition of key concepts is followed by a brief synthetic introduction of each selected (con)federation and international organisation, as well as an analysis of how the principle of equality amongst their units/Member States is normatively defined and practically applied. The discussion emphasises the principle’s importance, its implications, and the challenges it poses in promoting cooperation amongst units/Member States within each selected state/organisation.